2014
DOI: 10.1002/gps.4148
|View full text |Cite
|
Sign up to set email alerts
|

Period, birth cohort and prevalence of dementia in mainland China, Hong Kong and Taiwan: a meta‐analysis

Abstract: ObjectiveThere have been dramatic societal changes in East Asia over the last hundred years. Several of the established risk factors could have important period and cohort effects. This study explores temporal variation of dementia prevalence in mainland China, Hong Kong and Taiwan taking study methods into account.MethodsSeventy prevalence studies of dementia in mainland China, Hong Kong and Taiwan were identified from 1980 to 2012. Five period groups (before 1990, 1990 ∼ 1994, 1995 ∼ 1999, 2000 ∼ 2004 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 36 publications
(45 reference statements)
3
37
0
Order By: Relevance
“…In China, which has the largest population of people with dementia, the prevalence of dementia appears to have increased steadily between 1990 and 2010 2 , 3 . However, this trend might be partly attributed to temporal variations in the methods used to estimate such prevalence 4 . The results of a national survey in 2008–2009 indicated that dementia was more common in rural areas than in urban settings 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In China, which has the largest population of people with dementia, the prevalence of dementia appears to have increased steadily between 1990 and 2010 2 , 3 . However, this trend might be partly attributed to temporal variations in the methods used to estimate such prevalence 4 . The results of a national survey in 2008–2009 indicated that dementia was more common in rural areas than in urban settings 5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this increasing trend could be a function of changes in study designs and methodological factors such as diagnostic criteria, which have been revised considerably in the past 30 years. A systematic review taking these into account did not show significant changes, and that there is major heterogeneity between studies (Wu et al ., 2014). Prevalence estimates in the studies using newer diagnostic criteria such as the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) and 10/66 diagnostic algorithm are systematically and significantly higher than those using older diagnostic criteria such as the Diagnostic and Statistical Manual of Mental Disorders, Third Edition (DSM-III), Diagnostic and Statistical Manual of Mental Disorders, Third Edition, Revised (DSM-III-R), Chinese Classification of Mental Disorders (Wu et al ., 2013).…”
Section: Results: a Synthesis Of The Evidence In East Asian Countriesmentioning
confidence: 99%
“…Considering the rise of non-communicable diseases in East Asian countries, the prevalence of dementia could indeed increase in the next few decades. This includes China, the country with the largest population in the world, even though the trend of prevalence has not significantly increased over the last 30 years (Wu et al ., 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The authors report a substantial increase of dementia prevalence in mainland China with a doubling of age-specific prevalence from 1990 to 2010 [32,34]. However, this pattern could be largely attributed to variation of study designs and methodological factors as these are significantly related to heterogeneity of prevalence studies in China [35,36]. Higher prevalence was found in the recent studies using newer diagnostic criteria (DSM-IV and 10/66 algorithm) than those using older diagnostic criteria (DSM-III, DSM-III-R and CCMD).…”
Section: Lower-and Middle-income Countries: Global Prevalence Of Demementioning
confidence: 99%